Nudging Generosity: Choice Architecture and Cognitive Factors in Charitable Giving - Jonathan F. Schulz; Petra Thiemann; Christian Thöni (Institute of Labor Economics (IZA), 2017)
In an experimental setup we investigate the effect of two different choice architectures on donation decisions. In the treatment group, subjects can either specify a charity of their choice, or select one from a list of five well-known charities; in the control group we do not provide a list. In a sample of 869 subjects we find a large treatment effect: Offering a list of default charities doubles the fraction of donors, as well as the revenue for charities. We find that the treatment intervention particularly affects subjects who tend to make intuitive choices.
Keywords: C93; D64; H41; L3; 330; charitable giving; donation; choice architecture; defaults; affective reactions